The Translation of Clausal Extension Collocation: A Contrastive Study of English-IndonesianTranslation - Ni Luh Putu Setiarini (Makassar State University, 2022)
Abstract. Collocation is the co-occurrence of words comprising a node and one or more collocates. Insufficient studies have documented on the equivalence of source language (SL) collocation into more than one version of target language (TL) collocation. Hence, this study aims to explore the equivalence of English clausal extension collocations in the three versions of Indonesian translated novels, to identify the typology of the translations, to deal with the cohesive ties of the translations, to investigate the translation techniques used, and to observe the impact of translation techniques on the quality of the translation in terms of accuracy, acceptability, and readability. The methods applied in this research were quantitative and descriptive qualitative. The data were taken from a novel Pride and Prejudice and the three versions of Indonesian translated novels. Documentary analysis was implemented in collecting the data. They were pinpointed, coded, evaluated, classified and analysed. Further, the findings indicate that English clausal extension collocations are translated into Indonesian in the form of clausal extension, verbal extension, clausal enhancement, verbal enhancement collocation, and non-verbal node collocation. Meanwhile, the cohesive ties of the collocations include strong and weak cohesive ties. The translation techniques applied are generalization, established equivalence, modulation, amplification, and discursive creation. The use of generalization, established equivalence, modulation and amplification results in accurate, acceptable, and readable translations. On the other hand, discursive creation and deletion result in less accurate, less acceptable and less readable. It was concluded that it is the arbitrariness of language that results the different typology and cohesive tie of collocation among languages. Altogether, accuracy, acceptability and readability should be the goal of translation. Keywords: Arbitrariness; Clausal Extension Collocation, Translation Quality Assessment, Translation Techniques